Dyskurs telewizyjny. Tytuły polskiej telewizji dziewcząt i chłopców = The television discourse. Headlines of polish television for girls and boys - Loewe, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
151 titles of Polish programmes for children and youth aired on Polish television since it was founded in 1956 have been subject to analysis and text interpretation. Using the stylistic and pragmatic analysis as well as the method of linguistic picture of the world the author outlines the dominant strategies used by the sender. The text contains reflections on the state of research on the child as the recipient of media messages and on the programme titles as metatextual elements.
Keywords: tytuły; telewizja; metatekst; nominacja; deskryptywność; headlines; television; metatext; nomination; description